Effect of substitution of [Pd(PPh3)(4)] by related compounds as catalysts in reactions of organic syntheses - Barbieri, R. S.; Bellato, C. R.; Dias, AKC; Massabni, A. C. (Springer, 2006)
The effect of substitution of [Pd(PPh3)(4)], which is unstable in air, by complexes of the type [MCl2L2] (M = Pd, Pt; L = AsPh3, SbPh3), [PdL4](L = PPh3, AsPh3, SbPh3) and [NiX2(PPh3)(2)] on the syntheses of thioethers, acetylenes and ketones is described.
Keywords: homogeneous catalysts; palladium complexes; platinum complexes; nickel complexes